The Role of Mobile Technology and Cloud Computing in Digital Education: A Literature Review - Zahmi, April; Judijanto, Loso; Refariza, Elva; Zahari, Iqlima; Fauzi, Muhammad Sukron (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of mobile technology and cloud computing has brought significant changes in the transformation of education towards a more flexible and inclusive digital learning ecosystem. This study aims to examine the role of mobile technology and cloud computing in digital education through a literature review method. The review analyzes various relevant scientific publications from 2018 to 2023 obtained from databases such as Google Scholar, JSTOR, ScienceDirect, and IEEE Xplore. Data analysis is conducted using a thematic analysis approach to identify patterns, benefits, and challenges of applying these two technologies in the context of education. The findings show that mobile technology plays a crucial role in expanding learning access without the limitations of space and time, while cloud computing supports the efficient management and distribution of learning materials and enhances collaboration between students and instructors. However, the implementation of these technologies still faces several challenges, including the digital divide, limited digital competence among educators, and issues of data security and privacy. Overall, mobile technology and cloud computing have great potential in improving the quality, accessibility, and sustainability of digital education if supported by adequate infrastructure, appropriate policies, and capacity building for human resources in education.